Heat transfer and fouling deposition investigation on the titanium coated heat exchanger surface - Oon C.S.; Kazi S.N.; Hakimin M.A.; Abdelrazek A.H.; Mallah A.R.; Low F.W.; Tiong S.K.; Badruddin I.A.; Kamanger S. (Elsevier B.V., 2023)
Calcium carbonate; Corrosion resistance; Corrosion resistant coatings; Fouling; Heat resistance; Heat transfer performance; Metal coatings; Physical vapor deposition; Textures; Coated heat exchanger; Coating material; Enhanced heat transfer; Fouling depositions; Fouling mitigation; Heat exchanger performance; Heat transfer resistance; Surface textures; Heat exchangers; calcium carbonate; titanium; Article; biofouling; coating (procedure); conductance; corrosion; flow rate; heat transfer; microscopy; physical vapor deposition